Identifikasi Tingkat Penjualan Produk Herbal HWI Menggunakan Algoritma C4.5 - Refni Sulastri (SAFE-Network, 2022)
Herbal stokist HWI Benai has several products that are most in demand by customers, including Vinmory, Habaolive Honey, Slimming Juice etc. However, HWI Benai's great stokist often runs out of stock of these best selling products due to the absence of reguler bookkepping, so customers turn to stockists who have more product. This study aims to make it easier for HWI herbal stockists in Benai to supply more goods based on the products that are most in demand by customers. The data needed is based on variables including product name, product item, unit qty, total, price and subtotal. From this data, Unit wty, total, price and subtotal. From this data, it will help in the processof knowing which products are most in demand based on the accuracy values obtained using the RapidMiner software. The method of the method using a decision tree. The result of the study obtained variables that affect the results in determining the best selling product including the number of orders, product types, purchasing status and customer status. From some if these variables can determine the highest accuracy value and produce a decision tree. The conclusion of this study is that the best method in determining the level of best selling sales is one of them using the C4.5 Algorithm. The C4.5 algorithm is an algorithm in form of a classification in the form of rules thath change the results of complex decision to be simpler and easier to understand